Differences in chronic spontaneous urticaria between Europe and Central/ South America: results of the multi-center real world AWARE study (2018)
ABSTRACT: Background: Global chronic urticaria (CU) disease experience and management is not well documented. This study descriptively compares these aspects among CU patients residing in Europe (EU) and Central and South America (C/SA). Methods: AWARE (A World-wide Antihistamine-Refractory chronic urticaria patient Evaluation) is a global prospective, non-interventional study of CU in the real-world setting. Patients were ≥ 18 years with a diagnosis of H1-antihistamine-refractory CU for > 2 months. Differences between the EU and C/SA regions in demographic and clinical characteristics, quality of life (QoL), work and activity impairment, pharmacological treatment, and healthcare resource use were examined. Results: In total, 4224 patients were included in the analysis (C/SA 492; EU 3732). Rates of untreated patients were greater in the C/SA region (45.1% vs. 31.9%; P < 0.005) and escalation to third-line therapy was rare in both regions. Differences in disease experience emerged, with C/SA patients more commonly experiencing angioedema (C/SA 50.8% vs. EU 46.1%; P = 0.03) or comorbid chronic inducible urticaria (C/SA 30% vs. EU 22%; P < 0.001). Correspondingly, rates of uncontrolled urticaria were higher among C/SA patients (82.8% vs. 77.5%; P = 0.017) and patients in the C/SA region showed significantly greater work and activity impairment (absenteeism: 10.4 ± 19.7 vs. 6.7 ± 19.0, P = 0.004; presenteeism: 30.3 ± 31.9 vs. 24.4 ± 25.8, P = 0.001; work productivity loss: 33.9 ± 33.9 vs. 26.5 ± 27.5, P < 0.001; activity impairment: 37.7 ± 34.7 vs. 32.7 ± 30.1, P = 0.001). However, QoL impairment was greater in the EU region (Dermatology Life Quality Index: C/SA 6.5 ± 5.9 vs. EU 8.3 ± 7.0; P < 0.001). There was a significant difference in use of healthcare resources, including emergency services (39.6% vs. 29.3%; P < 0.001), hospitalization (7.7% vs 21.9%; P < 0.001) general practitioners (31.7% vs 57.3%; P < 0.001), and additional allergists or dermatologists (50.6% vs. 47.3%, P < 0.001), among patients in the C/SA and EU region, respectively. In both regions, patients with a primary diagnosis of CU with angioedema had significantly greater impairment in work and non-work activities and healthcare resource utilization compared to those without angioedema. Conclusions: This study revealed that CU is a heterogeneous condition with differences in healthcare utilization and outcomes between EU and C/SA. However, overall there is a high unmet need of H1-antihistamine-refractory CU patients, which is associated with high use of healthcare resources, and has a large negative effect on QoL and work productivity. Keywords: Angioedema; Chronic spontaneous urticaria; Quality of life; Urticaria.